Punção em lajes lisas unidirecionais de concreto armado com diferentes taxas de armadura secundária e pilares retangulares. - BRANCO, Vitor Hugo Lopes (Universidade Federal do Pará, 2023)
Symmetric punching tests and experimental analyses were conducted to evaluate the behavior of nine one-way reinforced concrete flat slabs. The slabs measured (1800 x 1800 x 120) mm, and loads were applied through three types of columns: A (85 × 85) mm, B (85 × 255) mm and C (85 × 425) mm. All slabs were made with constant longitudinal reinforcement ratio at around 1% (ρx) and different secondary flexural reinforcement ratios (ρy), namely type 1 (0.5%), type 2 (1%) and type 3 (2%), approximately. Concrete compressive strength of 28 MPa and elasticity modulus of 27 GPa. Reinforcement yield stress of 573 MPa and elasticity modulus of 244 GPa. Column rectangularity index (cmax/cmín) and secondary reinforcement ratio were the main research variables, and the present study evaluated their influence on the ultimate punching strength of the sampled one way reinforced concrete flat slabs. The experimental results were compared with four current international standards: ACI 318 (2019), EC2 (2004), MC 2010 (2011) and NBR 6118 (2014). They were also compared with the findings from a nonlinear numerical analysis made with the software ABAQUS CAE 6.14, based on the Finite Element Method (FEM) and on the Concrete Damage Plasticity (CDP) model. The results indicated that the standards need to be updated, and that there is a proportional increase of up to 50% approximately in slab punching strength when the secondary reinforcement ratio is increased by up to 2%.